2014
DOI: 10.1038/srep06697
|View full text |Cite
|
Sign up to set email alerts
|

Higher omega-3 index is associated with increased insulin sensitivity and more favourable metabolic profile in middle-aged overweight men

Abstract: We assessed whether omega-3 index (red blood cell concentrations of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) was associated with insulin sensitivity and other metabolic outcomes in 47 overweight men aged 46.5 ± 5.1 years. Participants were assessed twice, 16 weeks apart. Insulin sensitivity was assessed by the Matsuda method from an oral glucose tolerance test. Linear associations were examined; stratified analyses were carried out with participants separated according to the omega-3 index: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 63 publications
5
59
1
Order By: Relevance
“…Several studies suggested the usefulness of n-3 PUFAs in DM2 prevention [21–23]. Nevertheless, the effect of n-3 PUFAs in those studies might have been stronger due to the lack of DM2 and lower degree of metabolic disturbances as compared to our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Several studies suggested the usefulness of n-3 PUFAs in DM2 prevention [21–23]. Nevertheless, the effect of n-3 PUFAs in those studies might have been stronger due to the lack of DM2 and lower degree of metabolic disturbances as compared to our study.…”
Section: Discussioncontrasting
confidence: 66%
“…There is evidence demonstrating that obese children and adults have low levels of circulating essential fatty acids including DHA, which could then impair many aspects of innate and adaptive immunity (3033, 60). The reduction in DHA levels in obese subjects could be driven by low consumption of essential fatty acids in the diet and/or potential genetic modifications to key enzymes that metabolize DHA (33). We did not assay for circulating levels of essential fatty acids in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Essential long chain n-3 polyunsaturated fatty acids (PUFA) are of interest given their immunomodulatory properties (30). Furthermore, plasma levels of long chain n-3 PUFAs are low in obese individuals compared to lean controls, which could contribute toward impairments in humoral immunity (3133). The two major long chain n-3 PUFAs of interest are eicosapentaenoic and docosahexaenoic (DHA) acids, which can have anti-inflammatory effects but their influence on B-cell activity is far less known (30).…”
Section: Introductionmentioning
confidence: 99%
“…Increased dietary intake of ω-3 fatty acids is generally accepted to promote leanness by increasing adaptive hormone release from the endocrine pancreas (46,47). eCBs are derived from arachidonic acid (20:4), an ω-6 PUFA.…”
Section: -Ag Signaling Modulates β Cell Survival In Pancreatic Pseudmentioning
confidence: 99%